2007
DOI: 10.1186/1471-2334-7-102
|View full text |Cite
|
Sign up to set email alerts
|

The prevalance, epidemiology and risk factors for onychomycosis in hemodialysis patients

Abstract: Background: Onychomycosis has a high prevalance among immunocompromised patients such as diabetics and hemodialysis patients. In the present study, we aimed to investigate the prevalence of onychomycosis among hemodialysis patients with and without diabetes mellitus, and to find out the factors likely to be associated with the development of onychomycosis among hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
(26 reference statements)
6
30
3
2
Order By: Relevance
“…8 In patients with chronic renal failure undergoing hemodialysis, concern with the type of therapy and assurance of an effective medication is even greater given the high prevalence of dermatophytosis in these patients and the high rate of therapeutic failure. [7][8][9] Oral treatment with antifungal agents such as terbinafine, itraconazole, ketoconazole and fluconazole represents the treatment of choice for dermatophytoses that fail to respond to topical medication. 16 Nevertheless, the use of these medications may result in undesirable side effects in the patient.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…8 In patients with chronic renal failure undergoing hemodialysis, concern with the type of therapy and assurance of an effective medication is even greater given the high prevalence of dermatophytosis in these patients and the high rate of therapeutic failure. [7][8][9] Oral treatment with antifungal agents such as terbinafine, itraconazole, ketoconazole and fluconazole represents the treatment of choice for dermatophytoses that fail to respond to topical medication. 16 Nevertheless, the use of these medications may result in undesirable side effects in the patient.…”
Section: Tablementioning
confidence: 99%
“…[4][5][6] The risk factors associated with dermatophytoses include aging, immunosuppression, a family history of diabetes mellitus, peripheral vascular disease, skin-related disorders such as hyperhidrosis and psoriasis, the use of tight-fitting footwear and trauma to the nails. 7 Studies have shown that patients with chronic renal failure are more susceptible to dermatophytosis, principally onychomycosis, which is the second most common disorder in patients undergoing hemodialysis, with a prevalence that ranges from 6.2 to 69.8%. [7][8][9] Onychomycosis is one of the most difficult dermatological conditions to treat and according to some authors therapeutic failure ranges from 20% to 50%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…and the second for patients with more than one year as shown in table (4); for the first group the signs and symptoms were as the following; headache in 11 patients, insomnia in 7 patients, convulsion in one patient, fine tremor in 6 patients, flapping tremor in one patient, no one with cranial neuropathy, periodic limb movement in 3 patients, one with restless leg syndrome, distal weakness in 2 patients, proximal As shown in table (6) Table( (28) and similar to the results of Güven K. and et al From Turkey in 2007 where the mean age was 54.6 years of 109 hemodialysis patients, this distribution can be due to increased prevalence of renal impairment in elderly, increased survival on hemodialysis and increased efficacy and more developed instrumentations for creation of vascular access even in the elderly. (29) In the study as shown in table (1) we have (56.8%) males and (43.2%) females while in Sudan Albbashir H. had a male to female ratio of 2:1 (28) and Nemanja Jonić from Serbia at 2008 showed that from overall number of patients included, (67.2%)of the men and (32,9%) women, (30) patterns in the incidence of kidney disease across gender are generally consistent, with higher rates occurring in men than in women. Similarly, men are reported to have greater rates of progression of non-diabetic CKD for some specific types of kidney disease, especially compared with premenopausal women.…”
Section: Resultsmentioning
confidence: 99%